Odpowiedź :
Odpowiedź:
1.
f(x) = 3 x + 1
Ma być a2 = a1 = 3, więc
g(x) = 3 x +b i P(-2,3)
zatem
3 = 3*(-2) + b
3 = -6 + b
b = 3 + 6 = 9
Odp. g(x) =3 x + 9
=================
2. A(-1,3) B(12,5)
f(x) = a x + b
3 = -1 a + b
5 = 12 a + b
---------------- odejmujemy stronami
5 - 3 = (12 a + b) - ( -a + b)
2 = 13 a / : 13
a = [tex]\frac{2}{13}[/tex]
b = 3 + a = 3 +[tex]\frac{2}{13}[/tex] = 3 [tex]\frac{2}{13}[/tex]
f(x) = [tex]\frac{2}{13}[/tex] x + 3 [tex]\frac{2}{13}[/tex]
================
3. f(x) = ( 6 -3 m) x + 3
g(x) = -3 x + 1
Musi zachodzić: 6 - 3 m = - 3
6 + 3 = 3 m
9 = 3 m /: 3
m = 3
============
Szczegółowe wyjaśnienie: